Uso de benzodioxolas em sistemas de fotoiniciação de adesivos odontológicos - Lima, Giana da Silveira (2009)
The objective of this study was to evaluate the effectiveness of benzodioxole derivatives as co-initiators of radical polymerization of experimental self-etching adhesive systems. To compose the experimental self-etching adhesive systems a primer, containing methacrylate monomers and solvents, was developed. A monomer mixture, based on 50 wt % of Bisphenol A glicidyl dimethacrylate (Bis-GMA), 25 wt% of triethyleneglycol dimethacrylate (TEGDMA) and 25 wt% of 2-hydroxyethyl methacrylate(HEMA), was used as a model dental adhesive resin. Camphorquinone (CQ) 1 mol % was used as a photoinitiator to initiate polymerization. Different co-initiators (1,3- benzodioxole and piperonyl alcohol) and concentrations (0.25, 0.50, 1, 2, 4, 8, 16 mol %) were used in a model dental adhesive resin, to compose the experimental groups. Additionally, tertiary amine (EDAB) was used as co-initiator in the control group. The physical, chemical and mechanical properties and characteristics of the polymer obtained for the experimental adhesives (ABDO, APA, AEDAB) were evaluated using polymerization kinetics, sorption and solubility, flexural strength and elastic modulus. The microtensile bond strength (µTBS) to enamel and dentin, and fracture mode were investigated. Adicionalmente morphological analysis of the dentin bonding Interface were evaluated. The results indicated that the BDO and PA were effective co-initiators for the photoinitiator system based on CQ. Comparisons between the benzodioxole derivative co-initiators and traditionally used amine EDAB, showed similar performance in the kinetics of polymerization, flexural strength, water sorption and solubility of the model dental adhesive resin evaluated. In the microtensile bond strength dentin means were higher than enamel and mixed failures were predominant. APA showed higher bond strengths than AEDAB, while ABDO showed intermediate data. The hybrid layer for all groups was shown to be shallow (1-2 µm thick). No appreciable differences in homogeneity were detected along the bonded interface. BDO and PA were feasible alternatives to conventional amine as co-initiator of radical polymerization, moreover, as these benzodioxoles are found in the human diet, this characteristic made them more promising and advantageous to use in dental adhesive resin formulations than amine.